Microstrip‐line‐slot fed EDPA elements and array with ELP. Issue 12 (1st September 2016) - Cao, Wen‐quan; Hong, Wei; Cai, Yang
Abstract : Equally divided patch antenna (EDPA) element and array designs with electrically large property (ELP) are proposed in this study. ELP is realized by dividing the square radiating patch into n × n ( n = 1, 2, 3, 4, 5, 6, …) elements gradually with the same overall size but higher resonant frequencies. The dispersion diagrams of the divided unit cells are extracted from the S‐parameters and the field characteristics of dominant modes are described to confirm the ELP. Then 4 × 4 EDPA is taken as an example for detail analysis. By optimizing the geometry of the microstrip‐line‐slot feeding structure, different resonant modes can be merged and broad bandwidth is achieved. Furthermore, 1 × 2 array of the 4 × 4 EDPA is designed. Both the element and array antennas were fabricated for verification and good agreement between the measured and simulated results was obtained. The element and array owns −10 dB impedance bandwidth of 51.4 and 34.9% and maximum gain of 10.6 and 13.5 dBi, respectively. The proposed EDPA method can be used to design antenna element and array with ELP in higher‐frequency band of microwave and millimetre‐wave band for their easy fabrication, wide bandwidth, and considerable gain property.